Mitophagy in ototoxicity - Han, Hezhou; Hu, Sainan; Hu, Yue; Liu, Dongliang; Zhou, Junbo; Liu, Xiaofang; Ma, Xiulan; Dong, Yaodong (Frontiers in Cellular Neuroscience, 2023)
Mitochondrial dysfunction is associated with ototoxicity, which is caused by external factors. Mitophagy plays a key role in maintaining mitochondrial homeostasis and function and is regulated by a series of key mitophagy regulatory proteins and signaling pathways; the results of ototoxicity models indicate the importance of this process in the etiology of ototoxicity. A number of recent investigations of the control of cell fate by mitophagy have enhanced our understanding of the mechanisms by which mitophagy regulates ototoxicity and other hearing-related diseases, providing opportunities for targeting mitochondria to treat ototoxicity.